Inefficiencies in Norwegian Small-scale Construction, or the Problem of too Long Trucks?. (2017) - Eivindson, Espen; Innvær, Berner E.; Kolberg, Elisabeth; Merschbrock, Christoph; Rolfsen, Christian Nordahl
Abstract: "When the truck arrived at the construction site it could not unload the material because it [the truck] was too long, we had to send it away […], this happens all the time in Oslo where we have to build on very small plots." (Carpenter, Oslo). As the quote illustrates, inefficiencies and resulting low productivity remain a challenge for today's small construction businesses. While the reasons for inefficiencies are not completely understood, various techniques for project planning and control have proven their practical value in mitigating them. Lean construction has been articulated as one of the concepts that can solve inefficiency problems. The national initiative "Lean construction Norway" initiated by government, academia, and industry, seeks to diffuse lean production principles in the construction industry. However, small to medium sized contractors remain largely excluded from the innovative practices. This article sets out to study what a small Norwegian contractor enforcing lean concepts in addressing construction inefficiencies may gain. Ingrained in the concept of muda we exemplify waste related to waiting, overproduction, defects, inventory, motion, over processing, and transporting. We ran a case study in a small industry standard type of residential project executed by a small contractor. Data were collected based on a series of qualitative interviews conducted with the on-site personnel. The findings illustrate a variety of inefficiencies resulting in low productivity. We expect that management inspired by lean principles in conjunction with modern planning methods such as building information modelling may improve project delivery in Norwegian small-scale construction.